2015
DOI: 10.1186/s13012-015-0230-4
|View full text |Cite
|
Sign up to set email alerts
|

Applying normalization process theory to understand implementation of a family violence screening and care model in maternal and child health nursing practice: a mixed method process evaluation of a randomised controlled trial

Abstract: BackgroundIn Victoria, Australia, Maternal and Child Health (MCH) services deliver primary health care to families with children 0–6 years, focusing on health promotion, parenting support and early intervention. Family violence (FV) has been identified as a major public health concern, with increased prevalence in the child-bearing years. Victorian Government policy recommends routine FV screening of all women attending MCH services. Using Normalization Process Theory (NPT), we aimed to understand the barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 30 publications
6
97
1
1
Order By: Relevance
“…The CHCN did, however, express a hesitance towards asking about IPV at home visits. This is somewhat contrary to findings in a RCT in Australia, where the maternity and child healthcare nurses participating in a structured screening and care model for IPV were found to gradually feel safer at home visits, as compared to the nurses in the control group (Hooker et al., ). Jack, Jamieson, Wathe, and MacMillan () found that universal screening for IPV using a standard set of questions was difficult to implement during home visits to a general population of new mothers.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…The CHCN did, however, express a hesitance towards asking about IPV at home visits. This is somewhat contrary to findings in a RCT in Australia, where the maternity and child healthcare nurses participating in a structured screening and care model for IPV were found to gradually feel safer at home visits, as compared to the nurses in the control group (Hooker et al., ). Jack, Jamieson, Wathe, and MacMillan () found that universal screening for IPV using a standard set of questions was difficult to implement during home visits to a general population of new mothers.…”
Section: Discussioncontrasting
confidence: 82%
“…However, the findings of this study also suggest that nurses may need more training to ask new mothers about IPV. This is in line with the abovementioned Australian study, where ongoing training was empathised by the nurses involved in screening for IPV within maternal and child health care (Hooker et al., ). Also Gutmanis, Beynon, Tutty, Wathen, and MacMillan () found that nurses’ and physicians’ educational and experiential preparedness emerged as a key factor that facilitate routinely initiating the topic of IPV.…”
Section: Relevance To Clinical Practicesupporting
confidence: 85%
See 2 more Smart Citations
“…, Hooker et al . , ). In addition, this study identified the ‘universality’ of the HV service and increased provision of home visits as a key area of concern.…”
Section: Resultsmentioning
confidence: 99%